The crystal structure of (RS)-7-chloro-2-(2,5-dimethoxyphenyl)-2,3-dihydroquinazolin-4(1H)-one: two hydrogen bonds generate an elegant three-dimensional framework structure - Kereyagalahally H. Narasimhamurthy; Chandra; Belakavadi K. Sagar; Kanchugarakoppal S. Rangappa; Hemmige S. Yathirajan; Christopher Glidewell (Acta Crystallographica Section E: Crystallographic Communications, 2019)
In the title compound, C61H15ClN2O3, the heterocyclic ring adopts an envelope conformation, folded across the N...N line, with the 2,5-dimethoxyphenyl unit occupying a quasi-axial site. There are two N—H...O hydrogen bonds in the structure: one hydrogen bond links molecules related by a 41 screw axis to form a C(6) chain, and the other links inversion-related pairs of molecules to form an R22(8) ring. The ring motif links all of the chains into a continuous three-dimensional framework structure. Comparisons are made with the structures of some related compounds.